Development and Services of Public Information Systems to Increase Community Participation - Dinda Khairani; Icha Santika; Habiba Habiba; Nur Wahida Agustin Siregar; Ridho Yoandika; Galih Supraja (International Journal of Economic Research and Financial Accounting, 2025)
Public Information System Development is the process of designing, implementing and maintaining a technology-based system which aims to provide transparent, accurate and relevant access to information to the public. This development process involves analyzing user needs, designing a user-friendly interface, and integrating technology capable of handling large volumes of data efficiently. Apart from that, security and privacy aspects are a major concern in ensuring that public data is not misused. Challenges in developing this system include differences in people's technological literacy levels, uneven technological infrastructure, and the need to comply with applicable regulations. With a collaborative development strategy, involving the government, developers and the community, this system is expected to increase transparency, participation and the quality of public services. Development of Public Information Systems also plays an important role in supporting inclusive and sustainable digital transformation in various sectors of life.